Research ethics in the context of a developing country: perspectives from Pakistan - Malik, A (2013)
The overarching rationale of research ethics guidance is that human participants should not be exploited when contributing to the good of science and society. Two essential requisites for this are that human participants consent voluntarily after being informed about a research trial and that benefits and risks are distributed fairly. With the increasingly global practice of biomedical research, fulfilling these requisites creates challenges in some contexts. I examine the challenges of applying these ethical requirements when patients are enrolled into research trials in Pakistan, with reference to the moral reasoning employed by researchers to negotiate these challenges. Using insights obtained from interviewing physicians conducting research and patients in tertiary-care hospitals, and from observing the interactions between these physician-researchers and patients in the context of research trial enrolment, I demonstrate how the socio-cultural environment in which research is carried out shapes the practice of ethics in important ways. I present the issue of informed consent as the core challenge. I also examine the implications for research of the researchers' view that their primary duty is that of a physician. The researchers determine the amount of information patients receive about research, guided in this by their sense of duty and influenced by their communication skills, time constraints and patients' education status. The process of decision-making is affected by such factors as the patients' gender, education level, financial independence and the role of other actors such as the spouse, relatives and the researcher. Commonly, a joint decision is reached after mutual consultation within the family, but sometimes patients may delegate or accept decisions made by the family, and occasionally the family's interest is inconsistent with the best health interest of the patient. This raises ethical challenges. When recording consent, a written consent is obtained because sponsors and guidelines require it and researchers prefer it. This emphasis on a written consent raises ethical challenges with regard to the ethical principle of respect for persons. I also argue that following the ethical principles of justice and equity are essential to avoiding exploitation when conducting research. Complex issues arise when guidance and local norms are at variance, or there is disagreement between local norms and fundamental rights. Their resolution requires sensitivity to, and awareness of, the context. Importantly, it is the commitment of those conducting research and at the interface with patients that determines the ethics of research. I conclude that upholding the spirit of the guidelines is more important than procedural intransigence.